A long-life lead paste formulation suitable for high-type reclining batteries and a method for preparing the same
Patent Information
- Application Number
- CN202610860259.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-15
- Publication Date
- 2026-10-13
AI Technical Summary
[0003]现有高型卧放贫液蓄电池若使用常规铅膏配方及制备工艺,则存在以下问题:正负极板在固化及化成过程中的收缩膨胀特性存在差异,在高型卧放电池极板竖直方向尺寸较大的结构下极易加剧极板弯曲变形,造成活性物质与集流体结合力下降、局部电流密度分布不均;同时,传统正极配方孔道结构单一、导电通路连续性不足,充电过程中易提前析气导致充电不充分,传统负极配方中硫酸铅晶体易粗大化生长引发极板钝化,正极活性物质也易出现腐蚀软化,不仅加快电池失水速度,还大幅缩短浮充使用年限
(1)本发明通过限定正极铅膏和负极铅膏具有相同的视密度,使正负极板在固化及化成过程中的收缩膨胀特性趋于一致,有效抑制了高型卧放电池结构中因极板竖直方向尺寸较大而加剧的极板弯曲变形,从而避免了活性物质与集流体结合力下降、局部电流密度分布不均的问题,显著提升了电池的结构稳定性和循环一致性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lead-acid battery technology, and particularly relates to a long-life lead paste formula and preparation method suitable for tall horizontal batteries. Background Technology
[0002] High-profile horizontally deployed starved electrolyte batteries are widely used in communication backup power supplies, uninterruptible power supply equipment, and other scenarios where the equipment operates under conditions of long-term float charging and frequent charging and discharging.
[0003] If conventional lead paste formulations and manufacturing processes are used in existing tall, horizontally placed, starved electrolyte batteries, the following problems exist: the positive and negative plates have different shrinkage and expansion characteristics during the curing and formation processes. In the case of tall, horizontally placed batteries with larger vertical dimensions of the plates, the bending deformation of the plates is easily aggravated, resulting in a decrease in the bonding force between the active material and the current collector, and uneven distribution of local current density. At the same time, the traditional positive electrode formulation has a simple pore structure and insufficient continuity of conductive pathways, which easily leads to premature gas evolution during charging, resulting in insufficient charging. In the traditional negative electrode formulation, lead sulfate crystals are prone to coarsening and growth, causing plate passivation. The positive electrode active material is also prone to corrosion and softening, which not only accelerates the battery's water loss rate but also significantly shortens the service life of float charging. Summary of the Invention
[0004] To address the problems in the prior art, the present invention proposes the following technical solution: This invention provides a long-life lead paste formulation suitable for tall, horizontally placed batteries, comprising: Positive electrode lead paste, wherein the positive electrode lead paste comprises the following components in parts by weight: 82-86 parts lead powder, 10-14 parts red lead, 7-11 parts deionized water, 10-14 parts dilute sulfuric acid, 0.10-0.15 parts 3D super-strong short fiber; The negative electrode lead paste comprises the following components by weight: 83-87 parts lead powder, 7-10 parts deionized water, 9-11 parts dilute sulfuric acid, 1.2-1.6 parts ultrafine barium sulfate, 0.2-0.35 parts acetylene black, 0.10-0.18 parts lignin, and 0.08-0.12 parts 3D ultra-strong short fiber; The apparent density of both the positive and negative electrode lead pastes is 4.25 g / cm³. 3 ~4.39g / cm 3 The positive and negative electrodes use the same apparent density, so that the shrinkage and expansion characteristics of the positive and negative electrode plates tend to be consistent during the curing and formation process, and suppress the bending deformation caused by the large vertical dimension of the electrode plates in the high-profile horizontal battery structure.
[0005] As a preferred embodiment of the above technical solution, in the positive electrode lead paste and the negative electrode lead paste, the density of the dilute sulfuric acid at 25°C is 1.325 g / ml.
[0006] As a preferred embodiment of the above technical solution, the positive electrode lead paste and the negative electrode lead paste have an oxidation degree of 72%~78%, pass through an 80-mesh sieve, and have an apparent density of 1.20~1.40 g / ml.
[0007] As a preferred embodiment of the above technical solution, the purity of the red lead in the positive electrode lead paste is ≥98%.
[0008] As a preferred embodiment of the above technical solution, the ultrafine barium sulfate in the negative electrode lead paste has a particle size ≤1μm and a purity ≥99%.
[0009] As a preferred embodiment of the above technical solution, according to the above-mentioned long-life lead paste formula suitable for high-profile horizontally placed batteries, the preparation method of the positive electrode lead paste and the negative electrode lead paste includes the following steps: S1. Powder mixing: Add all solid components into the paste mixer and mix them in a dry state. S2. Low-temperature wetting: Add deionized water at a uniform rate and control the slurry temperature to ≤30℃ through cooling water circulation; S3. Temperature-controlled acidification: Add dilute sulfuric acid at a uniform rate. When the system temperature reaches 58℃, turn on the exhaust fan and control the maximum temperature throughout the process to be ≤58℃. S4. Constant temperature discharge: After the acid is added, continue stirring for 3 minutes. When the temperature of the lead paste drops to ≤50℃, discharge the paste to obtain the finished lead paste.
[0010] As a preferred embodiment of the above technical solution, in step S1, the dry mixing and stirring time is 4 min to 5 min.
[0011] As a preferred embodiment of the above technical solution, in step S2, deionized water is added at a uniform rate within 60s to 90s, and stirring continues for 4min to 5min after the water is added.
[0012] As a preferred embodiment of the above technical solution, in step S3, dilute sulfuric acid is added dropwise at a uniform rate over a period of 12 to 18 minutes.
[0013] The beneficial effects of this invention are as follows: (1) By limiting the positive electrode paste and the negative electrode paste to have the same apparent density, the positive and negative electrode plates tend to have consistent shrinkage and expansion characteristics during the curing and formation process. This effectively suppresses the bending deformation of the electrode plates caused by the large vertical dimension of the electrode plates in the high-profile horizontal battery structure, thereby avoiding the problems of decreased bonding force between the active material and the current collector and uneven distribution of local current density, and significantly improving the structural stability and cycle consistency of the battery.
[0014] (2) By using the synergistic ratio of red lead and 3D super-strong short fibers in the positive electrode lead paste, the present invention constructs a continuous conductive network and a multi-level pore structure, which solves the problem of the single pore structure and insufficient continuity of the conductive path in the traditional positive electrode formulation. It effectively avoids the phenomenon of insufficient charging caused by premature gas evolution during charging, and greatly improves the charging efficiency and charging reception capability.
[0015] (3) This invention achieves the refinement of lead sulfate crystals and the stabilization of the pore structure of negative electrode active material through the synergistic effect of multiple components such as ultrafine barium sulfate, acetylene black, lignin and 3D ultra-strong short fibers in negative electrode lead paste. It effectively suppresses the plate passivation problem caused by the coarsening growth of lead sulfate crystals in traditional negative electrode formulations, while slowing down the corrosion and softening of positive electrode active material, significantly extending the service life of the battery during float charging, and reducing the long-term float charging water loss rate. Detailed Implementation
[0016] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments.
[0017] This invention ensures that the positive and negative electrode pastes have the same apparent density, making the shrinkage and expansion characteristics of the positive and negative electrode plates more consistent during the curing and formation process. In tall horizontally placed batteries, the vertical dimensions of the electrode plates are relatively large. If the apparent densities of the positive and negative electrodes are inconsistent, their shrinkage and expansion behaviors will differ, leading to additional stress inside the electrode plates and exacerbating the bending deformation of the plates. The design with the same apparent density eliminates the internal stress caused by asynchronous shrinkage and expansion from the root, effectively suppressing the bending deformation of the electrode plates and avoiding the problems of decreased bonding force between the active material and the current collector and uneven distribution of local current density.
[0018] Adding 10-14 parts of red lead to the positive electrode paste allows the red lead to be converted in situ into PbO2 during the paste mixing and curing process, forming a pre-formed nucleus system. Under high-profile horizontally placed, low-electrolyte conditions, the electrolyte exhibits a concentration gradient along the electrode height, with higher concentrations at the bottom and lower concentrations at the top. This leads to a lag and uneven formation of PbO2 in traditional positive electrodes. The pre-formed nucleus system can induce PbO2 deposition in the low-electrolyte region along the electrode height, compensating for the lag in PbO2 formation caused by uneven electrolyte distribution and guiding PbO2 to be evenly distributed throughout the entire electrode height. Simultaneously, the 3D ultra-strong short fibers in the positive electrode paste construct a multi-level porous structure ranging from micrometers to millimeters, forming continuous electrolyte storage and transport channels. This improves the wetting and diffusion efficiency of the electrolyte within the positive electrode, reduces ion migration resistance, effectively avoids premature gas evolution due to localized electrolyte deficiency during charging, and ensures sufficient charging.
[0019] A three-phase synergistic network of conductivity, crystal inhibition, and dispersion was constructed in the negative electrode lead paste: Acetylene black, with its high specific surface area and good conductivity, forms continuous conductive channels in the negative electrode. In the horizontally placed state, it facilitates a uniform distribution of charging current along the height of the electrode plate, avoiding localized overcharging or undercharging due to uneven current distribution. Ultrafine barium sulfate, acting as a heterogeneous nucleus, has lattice parameters similar to lead sulfate and can preferentially adsorb Pb. 2+ Lead sulfate is induced to crystallize on its surface. In tall horizontal batteries, the electrolyte exhibits stratification along the height of the plates, with higher electrolyte concentration and lead sulfate saturation at the bottom, easily leading to coarse growth of lead sulfate crystals. The numerous micro-nuclei of ultrafine barium sulfate provide ample crystallization sites, allowing lead sulfate to precipitate uniformly in the form of fine grains, effectively inhibiting the coarsening growth of lead sulfate crystals at the bottom and suppressing plate passivation. Lignin, as an anionic surfactant, has active groups on its molecular chain that can adsorb onto the surface of lead and lead sulfate particles. Through the dual effects of steric hindrance and electrostatic repulsion, it maintains the dispersion of active materials under low electrolyte conditions, preventing agglomeration and grain coarsening, and preserving the porous structure and reactivity of the negative electrode active material. Furthermore, the 3D ultra-strong short fibers in the negative electrode lead paste also construct a three-dimensional network structure, enhancing the overall binding strength of the negative electrode active material and preventing its shedding during cycling.
[0020] The pre-placed crystal nuclei with uniform distribution in the positive electrode and the three-phase synergistic network in the negative electrode complement each other. Red lead in the positive electrode guides the uniform distribution of PbO2 along the electrode height, ensuring the uniformity of the positive electrode charging reaction; acetylene black in the negative electrode facilitates the uniform distribution of charging current, ensuring the uniformity of the negative electrode charging reaction. Together, they prevent localized overcharging or undercharging caused by asynchronous charging reactions in the positive and negative electrodes. Simultaneously, the identical apparent density design of the positive and negative electrodes ensures the symmetry and stability of the electrode structure, providing a structural basis for the uniform conduction of the aforementioned electrochemical reactions.
[0021] The segmented temperature control process (low-temperature wetting ≤30℃, temperature-controlled acidification peak ≤58℃, constant-temperature paste discharge ≤50℃) provides a process guarantee for the optimal physical properties of the above formulation system, ensuring uniform fiber dispersion, stable red lead conversion, and uniformity of lead paste pore structure.
[0022] Example 1
[0023] In this embodiment, the lead powder has an oxidation degree of 75%, passes through an 80-mesh sieve, and has an apparent density of 1.30 g / ml; the red lead purity is 98.5%; and the ultrafine barium sulfate has a particle size of 0.9 μm and a purity of 99.3%.
[0024] The positive electrode lead paste is prepared using the following steps: 84 parts lead powder, 12 parts red lead, and 0.12 parts 3D ultra-strong short fiber were added to a paste mixing machine and dry-mixed for 4.5 minutes. Within 75 seconds, 9 parts deionized water were added at a uniform rate, and mixing continued for another 4.5 minutes after the water addition was complete. The slurry temperature was controlled to ≤30℃ using cooling water circulation. Within 15 minutes, 12 parts dilute sulfuric acid (density 1.325 g / ml at 25℃) were added dropwise at a uniform rate. When the system temperature reached 58℃, the exhaust fan was turned on, and the maximum temperature throughout the process was controlled to ≤58℃. After the acid addition was complete, mixing continued for 3 minutes. When the lead paste temperature dropped to ≤50℃, the paste was discharged, yielding the positive electrode lead paste with an apparent density of 4.32 g / cm³. 3 .
[0025] The negative electrode lead paste is prepared using the following steps: 85 parts lead powder, 1.4 parts ultrafine barium sulfate, 0.28 parts acetylene black, 0.14 parts lignin, and 0.10 parts 3D ultra-strong short fiber were added to a paste mixing machine and dry-mixed for 4.5 minutes. 8.5 parts deionized water were added uniformly over 75 seconds, and mixing continued for another 4.5 minutes, with the paste temperature controlled to ≤30℃ using cooling water circulation. 10 parts dilute sulfuric acid (density 1.325 g / ml at 25℃) was added dropwise uniformly over 15 minutes. When the system temperature reached 58℃, the exhaust fan was turned on, and the maximum temperature throughout the process was controlled to ≤58℃. After the acid addition was complete, mixing continued for 3 minutes. The paste was discharged when the temperature dropped to ≤50℃, yielding negative electrode lead paste with an apparent density of 4.32 g / cm³. 3 .
[0026] Example 2
[0027] In this embodiment, the lead powder oxidation degree is 72%, passes through an 80-mesh sieve, and the apparent density of the lead powder is 1.20 g / ml; the red lead purity is 98.0%; and the ultrafine barium sulfate particle size is 1.0 μm with a purity of 99.0%.
[0028] The positive electrode lead paste is prepared using the following steps: 82 parts lead powder, 13 parts red lead, and 0.13 parts 3D ultra-strong short fiber were added to a paste mixing machine and dry-mixed for 4 minutes. 10 parts deionized water were added uniformly over 60 seconds, and mixing continued for another 4 minutes, with the slurry temperature controlled to ≤30℃ using cooling water circulation. 13 parts dilute sulfuric acid were added dropwise uniformly over 14 minutes. When the system temperature reached 58℃, the exhaust fan was turned on, and the maximum temperature throughout the process was controlled to ≤58℃. After the acid addition was complete, mixing continued for 3 minutes. The paste was discharged when the temperature dropped to ≤50℃, yielding the positive electrode lead paste with an apparent density of 4.28 g / cm³. 3 .
[0029] The negative electrode lead paste is prepared using the following steps: 87 parts lead powder, 1.3 parts ultrafine barium sulfate, 0.20 parts acetylene black, 0.18 parts lignin, and 0.09 parts 3D ultra-strong short fiber were added to a paste mixing machine and dry-mixed for 5 minutes. 7 parts deionized water were added uniformly over 80 seconds, and mixing continued for 4.8 minutes after water addition, with the slurry temperature controlled to ≤30℃ using cooling water circulation. 11 parts dilute sulfuric acid were added dropwise uniformly over 12 minutes. When the system temperature reached 58℃, the exhaust fan was turned on, and the maximum temperature throughout the process was controlled to ≤58℃. After acid addition, mixing continued for 3 minutes. The paste was discharged when the lead paste temperature dropped to ≤50℃, yielding negative electrode lead paste with an apparent density of 4.28 g / cm³. 3 .
[0030] Example 3
[0031] In this embodiment, the lead powder oxidation degree is 78%, passes through an 80-mesh sieve, and the apparent density of the lead powder is 1.40 g / ml; the red lead purity is 99.0%; and the ultrafine barium sulfate particle size is 0.8 μm with a purity of 99.5%.
[0032] The positive electrode lead paste is prepared using the following steps: 86 parts lead powder, 10 parts red lead, and 0.10 parts 3D ultra-strong short fiber were added to a paste mixing machine and dry-mixed for 5 minutes. 7 parts deionized water were added uniformly over 90 seconds, and mixing continued for another 5 minutes, with the slurry temperature controlled to ≤30℃ using cooling water circulation. 10 parts dilute sulfuric acid were added dropwise uniformly over 18 minutes. When the system temperature reached 58℃, the exhaust fan was turned on, and the maximum temperature throughout the process was controlled to ≤58℃. After the acid addition was complete, mixing continued for 3 minutes. The paste was discharged when the temperature dropped to ≤50℃, yielding the positive electrode lead paste with an apparent density of 4.25 g / cm³. 3 .
[0033] The negative electrode lead paste is prepared using the following steps: 83 parts lead powder, 1.6 parts ultrafine barium sulfate, 0.35 parts acetylene black, 0.10 parts lignin, and 0.08 parts 3D ultra-strong short fiber were added to a paste mixing machine and dry-mixed for 4 minutes. 10 parts deionized water were added uniformly over 60 seconds, and mixing continued for 4 minutes after water addition, with the slurry temperature controlled to ≤30℃ using cooling water circulation. 9 parts dilute sulfuric acid were added dropwise uniformly over 18 minutes. When the system temperature reached 58℃, the exhaust fan was turned on, and the maximum temperature throughout the process was controlled to ≤58℃. After acid addition, mixing continued for 3 minutes. The paste was discharged when the lead paste temperature dropped to ≤50℃, yielding negative electrode lead paste with an apparent density of 4.25 g / cm³. 3 .
[0034] Example 4
[0035] In this embodiment, the lead powder oxidation degree is 76%, passes through an 80-mesh sieve, and has an apparent density of 1.35 g / ml; the red lead purity is 98.8%; and the ultrafine barium sulfate particle size is 0.85 μm with a purity of 99.2%. The positive electrode lead paste is prepared using the following steps: Add 85 parts lead powder, 14 parts red lead, and 0.15 parts 3D super strong short fiber to a paste mixer and mix in a dry state for 4.8 minutes. Add 11 parts of deionized water at a uniform rate over 85 seconds. After the water addition is complete, continue stirring for 4.2 minutes, and control the slurry temperature to ≤30℃ using cooling water circulation. Add 14 parts of dilute sulfuric acid dropwise at a uniform rate over 16 minutes. When the system temperature reaches 58℃, turn on the exhaust fan, and control the maximum temperature throughout the process to ≤58℃. After the acid addition is complete, continue stirring for 3 minutes. When the lead paste temperature drops to ≤50℃, discharge the paste to obtain the positive electrode lead paste, with an apparent density of 4.39 g / cm³. 3 .
[0036] The negative electrode lead paste is prepared using the following steps: 86 parts lead powder, 1.2 parts ultrafine barium sulfate, 0.25 parts acetylene black, 0.12 parts lignin, and 0.12 parts 3D ultra-strong short fiber were added to a paste mixing machine and dry-mixed for 4.5 minutes. Within 70 seconds, 9 parts deionized water were added at a uniform rate, and mixing continued for another 4.5 minutes, with the slurry temperature controlled to ≤30℃ using cooling water circulation. Within 15 minutes, 10 parts dilute sulfuric acid were added dropwise at a uniform rate. When the system temperature reached 58℃, the exhaust fan was turned on, and the maximum temperature throughout the process was controlled to ≤58℃. After the acid addition was complete, mixing continued for 3 minutes. The paste was discharged when the temperature dropped to ≤50℃, yielding negative electrode lead paste with an apparent density of 4.39 g / cm³. 3 .
[0037] Comparative Example 1 The positive electrode lead paste is prepared using the following steps: 80 parts lead powder, 8 parts red lead, and 0.12 parts ordinary short fiber were added to a paste-making machine, along with 9 parts deionized water and 12 parts dilute sulfuric acid (density 1.280 g / ml at 25°C). The mixture was stirred and mixed, then naturally heated to 65°C. The paste was dispensed at 55°C to obtain positive electrode lead paste with an apparent density of 4.20 g / cm³. 3 .
[0038] The negative electrode lead paste is prepared using the following steps: 80 parts lead powder, 1.0 part ordinary barium sulfate, 0.15 parts acetylene black, 0.08 parts lignin, and 0.10 parts ordinary short fiber were added to a paste-making machine, along with 9 parts deionized water and 10 parts dilute sulfuric acid (density 1.280 g / ml at 25℃). The mixture was stirred and mixed, then naturally heated to 65℃. The paste was dispensed at 55℃ to obtain negative electrode lead paste with an apparent density of 4.30 g / cm³. 3 .
[0039] Comparative Example 2 The difference from Example 1 is that the apparent density of the positive electrode lead paste and the negative electrode lead paste are different, with the apparent density of the positive electrode lead paste being 4.20 g / cm³. 3 The apparent density of the negative electrode lead paste is 4.38 g / cm³. 3 The rest is the same as in Example 1.
[0040] Comparative Example 3 The difference from Example 1 is that no lignin is added to the negative electrode lead paste, and the amount of acetylene black is adjusted to 0.42 parts, while the rest is the same as in Example 1.
[0041] Comparative Example 4 The difference from Example 1 is that the conventional one-step paste-making process is adopted, in which all solid components are added to the paste-making machine at the same time with deionized water and dilute sulfuric acid, stirred and mixed, and naturally heated to 65°C. The paste exit temperature is 55°C, and the rest is the same as Example 1.
[0042] The lead pastes prepared in Examples 1-4 and Comparative Examples 1-4 were fabricated into electrode plates using the same process and assembled into high-profile horizontally discharged lean-liquid batteries (12V / 100Ah). Performance verification was performed, and the test results are shown in the table below: Test conditions: charging voltage 2.45V / cell, discharge termination voltage 1.80V / cell, float charge voltage 2.27V / cell, test temperature 25±2℃.
[0043] Table 1 As shown in Table 1, the lead pastes prepared in Examples 1-4 are significantly better than all comparative examples in terms of overall performance. Among them, Example 1 has a charging efficiency of 91.5%, a float charging life of 2100 cycles, and an internal resistance deviation controlled at 3.9%. All indicators are significantly better than traditional formulas. Comparative Example 1, using a conventional formula and process, verified the effectiveness of the overall technical solution of the present invention. Comparative Example 2, using the formula of the present invention but with inconsistent apparent densities of the positive and negative electrodes, showed lower performance than Example 1, verifying that identical apparent densities of the positive and negative electrodes make the shrinkage and expansion characteristics of the positive and negative plates more consistent, effectively suppressing plate bending deformation, which is one of the key technical features for improving the performance of high-profile horizontally placed batteries. Comparative Example 3, using the formula of the present invention but without lignin in the negative electrode, showed a significant decrease in charging efficiency and float charge life, verifying that lignin, as an expanding agent, has a synergistic effect with acetylene black, and that lignin can enhance the charging and discharging performance of batteries. During the charging process, the coarsening growth of lead sulfate crystals is suppressed, and the porous structure and reactivity of the negative electrode active material are maintained. Only through the combined effect of these two factors can the optimal performance of the negative electrode be achieved. Comparative Example 4 uses the formula of this invention but does not employ the segmented temperature control process. The active material shedding rate and float charge water loss rate are significantly increased. This verifies that the segmented temperature control process, through precise temperature control of low-temperature wetting, temperature-controlled acidification, and constant-temperature paste discharge, can avoid stress concentration and damage to the active material structure inside the lead paste, ensuring the uniformity of the lead paste pore structure and the overall strength of the electrode plate. This is an important guarantee for improving the structural stability of the lead paste and the cycle life of the battery.
[0044] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it.
Claims
1. A long-life lead paste formula suitable for tall, horizontally placed batteries, characterized in that, include: Positive electrode lead paste, wherein the positive electrode lead paste comprises the following components in parts by weight: 82-86 parts lead powder, 10-14 parts red lead, 7-11 parts deionized water, 10-14 parts dilute sulfuric acid, 0.10-0.15 parts 3D super-strong short fiber; The negative electrode lead paste comprises the following components by weight: 83-87 parts lead powder, 7-10 parts deionized water, 9-11 parts dilute sulfuric acid, 1.2-1.6 parts ultrafine barium sulfate, 0.2-0.35 parts acetylene black, 0.10-0.18 parts lignin, and 0.08-0.12 parts 3D ultra-strong short fiber; The apparent density of both the positive and negative electrode lead pastes is 4.25 g / cm³. 3 ~4.39g / cm 3 The positive and negative electrodes use the same apparent density, so that the shrinkage and expansion characteristics of the positive and negative electrode plates tend to be consistent during the curing and formation process, and suppress the bending deformation caused by the large vertical dimension of the electrode plates in the high-profile horizontal battery structure.
2. The long-life lead paste formula for high-profile horizontally placed batteries according to claim 1, characterized in that, In the positive and negative lead pastes, the density of the dilute sulfuric acid at 25°C is 1.325 g / ml.
3. The long-life lead paste formula for high-profile horizontally placed batteries according to claim 1, characterized in that, In the positive and negative electrode lead pastes, the oxidation degree of the lead powder is 72%~78%, and the apparent density of the lead powder is 1.20~1.40 g / ml after passing through an 80-mesh sieve.
4. The long-life lead paste formula for high-profile horizontally placed batteries according to claim 1, characterized in that, In the positive electrode lead paste, the purity of the red lead is ≥98%.
5. The long-life lead paste formulation for high-profile horizontally placed batteries according to claim 1 is characterized in that, In the negative electrode lead paste, the ultrafine barium sulfate has a particle size ≤1μm and a purity ≥99%.
6. The method for preparing a long-life lead paste formulation suitable for high-profile horizontally placed batteries as described in any one of claims 1-5, characterized in that: The preparation of both the positive and negative lead pastes includes the following steps: S1. Powder mixing: Add all solid components into the paste mixer and mix them in a dry state. S2. Low-temperature wetting: Add deionized water at a uniform rate and control the slurry temperature to ≤30℃ through cooling water circulation; S3. Temperature-controlled acidification: Add dilute sulfuric acid at a uniform rate. When the system temperature reaches 58℃, turn on the exhaust fan and control the maximum temperature throughout the process to be ≤58℃. S4. Constant temperature discharge: After the acid is added, continue stirring for 3 minutes. When the temperature of the lead paste drops to ≤50℃, discharge the paste to obtain the finished lead paste.
7. The method for preparing a long-life lead paste formulation suitable for high-profile horizontally placed batteries according to claim 6, characterized in that, In step S1, the dry mixing and stirring time is 4 min to 5 min.
8. The method for preparing a long-life lead paste formulation suitable for high-profile horizontally placed batteries according to claim 6, characterized in that, In step S2, deionized water is added at a constant rate over a period of 60 to 90 seconds, and stirring continues for 4 to 5 minutes after the water addition is complete.
9. A method for preparing a long-life lead paste formulation suitable for high-profile horizontally placed batteries according to claim 6, characterized in that, In step S3, dilute sulfuric acid is added dropwise at a constant rate over a period of 12 to 18 minutes.